Templated Growth and Passivation of Vertically Oriented Antimony Selenide Thin Films for High‐Efficiency Solar Cells in Substrate Configuration. (25th November 2021) - Rijal, Suman; Li, Deng‐Bing; Awni, Rasha A.; Xiao, Chuanxiao; Bista, Sandip S.; Jamarkattel, Manoj K.; Heben, Michael J.; Jiang, Chun‐Sheng; Al‐Jassim, Mowafak; Song, Zhaoning; Yan, Yanfa
Abstract: Antimony selenide (Sb2 Se3 ) is a promising low‐cost photovoltaic material with a 1D crystal structure. The grain orientation and defect passivation play a critical role in determining the performance of polycrystalline Sb2 Se3 thin‐film solar cells. Here, a seed layer is introduced on a molybdenum (Mo) substrate to template the growth of a vertically oriented, columnar Sb2 Se3 absorber layer by closed space sublimation. By controlling the grain orientation and compactness of the Sb2 Se3 seeds, obtain high‐quality Sb2 Se3 absorber layers with passive Sb2 Se3 /Mo interfaces is obtained, which in turn improve the transport of photoexcited charge carriers through the absorber layer and its interfaces. Post‐deposition annealing of absorber layers in ambient air is further utilized to passivate the defects in Sb2 Se3 and enhance the quality of the front heterojunction. As a result of systematic processing optimization, Sb2 Se3 planar heterojunction solar cells are fabricated in substrate configuration with a champion power conversion efficiency of 8.5%. Abstract : Controlling grain growth and passivating defects are essentially important for improving the photovoltaic performance of antimony selenide (Sb2 Se3 ) thin‐film solar cells. In this study, the seed‐layer templated growth and post‐air annealing is combined to prepare vertically oriented and passivated Sb2 Se3 films on molybdenum substrates. As a result, substrate configuration Sb2 Se3 solar cells with a champion efficiency of 8.5% are demonstrated.